A Convenient Synthesis of Fused Tetrahydroazocines from Acenaphthylene-1,2-dione, Proline, and Acetylenic Esters - Yavari, Issa; Baoosi, Leila; Halvagar, Mohammad Reza (Synlett, 2018)
A synthesis of dialkyl (12E,14E)-7-oxo-10,11-dihydro-7H,9H-azocino[2,1-a]benzo[de]isoquinoline-13,14-dicarboxylates through a 1,3-dipolar cycloaddition reaction of azomethine ylides, generated in situ from proline and acenaphthylene-1,2-dione, with dialkyl acetylenedicarboxylates is described. According to the X-ray diffraction data, the tetrahydroazocine ring has a rigid twist-boat form with approximate local C2 symmetry.
Keywords: tetrahydroazocines; acetylenic esters; azocinobenzoisoquinolines; 1,3-dipolar cycloaddition; azomethine ylides; proline